Astrocytic cytoskeletal atrophy in the medial prefrontal cortex of a triple transgenic mouse model of Alzheimer's disease - Kulijewicz-Nawrot, Magdalena; Verkhratsky, Alexei; Chvátal, Alexander; Syková, Eva; Rodríguez, José J (Journal of anatomy, 2012)
Alzheimer's disease (AD) is a progressive neurodegenerative disorder characterized by the loss of cognitive functions, reflecting pathological damage to the medial prefrontal cortex (mPFC) as well as to the hippocampus and the entorhinal cortex. Astrocytes maintain the internal homeostasis of the CNS and are fundamentally involved in neuropathological processes, including AD. Here, we analysed the astrocytic cytoskeletal changes within the mPFC of a triple transgenic mouse model of AD (3 × Tg-AD) by measuring the surface area and volume of glial fibrillary acidic protein (GFAP)-positive profiles in relation to the build-up and presence of amyloid-β (Aβ), and compared the results with those found in non-transgenic control animals at different ages. 3 × Tg-AD animals showed clear astroglial cytoskeletal atrophy, which appeared at an early age (3 months; 33% and 47% decrease in GFAP-positive surface area and volume, respectively) and remained throughout the disease progression at 9, 12 and 18 months old (29% and 36%; 37% and 35%; 43% and 37%, respectively). This atrophy was independent of Aβ accumulation, as only a few GFAP-positive cells were localized around Aβ aggregates, which suggests no direct relationship with Aβ toxicity. Thus, our results indicate that the progressive reduction in astrocytic branching and domain in the mPFC can account for the integrative dysfunction leading to the cognitive deficits and memory disturbances observed in AD.
Keywords: Prefrontal Cortex; cytoskelet; prefrontální mozková kůra; Mice, Transgenic; Atrophy; Disease Progression; myši transgenní; Alzheimer Disease; zvířata; Alzheimerova nemoc; myši; amyloidní beta-protein; Immunohistochemistry; imunohistochemie; atrofie; Mice; Amyloid beta-Peptides; Astrocytes; progrese nemoci; Animals; astrocyty; Disease Models, Animal; Cytoskeleton; modely nemocí na zvířatech